Majority Carry the Vote: Psycho-Demographic Influence on Voting Behaviour (2007)
The study examined the influence of psychological and demographic variables (age, ethnicity, sex, social class, media and self-esteem) on voting behaviour. 232 randomly selected participants (males and females) in Ibadan metropolis took part in the study. A questionnaire made up of 4 sections was used to collect information from the participants. A multiple regression revealed that of all the psycho-demographic variables only age and self-esteem independently predicted voting behaviour. Also, analysis of Variance showed an interaction effect of age and sex on voting behaviour (f ( I, 2 I 4) =7.26, P<.'05). Thus, it is recommended that appropriate authorities would provide a level playing ground for people of different age and sex to exercise their civic duties, also, mass mobilization aimed at voters being assertive in the election of their leaders should be embarked upon by both government and nongovernmental organizations in order to effect positive attitudinal change in the electorates.